(untitled) (Research, Society and Development, 2023)
Delivery services via mobile devices are already a reality in modern society. In the food sector, companies seek to invest in technology in order to improve their services, seeking advantages in an increasingly competitive market. The difficulty of retaining customers, managing consumer demands, and effectively applying promotions are just some of the obstacles present in this scenario, in addition to strong competition, which reinforces the importance of delivery applications as a powerful tool to help companies remain in the market. However, in less developed cities, there is still a lack of technology to help small entrepreneurs in this field, as is the case in the municipality of Princesa Isabel, Paraíba, Brazil. In this context, this work seeks to demonstrate the steps used to create a delivery application for pizzerias that aims to solve or reduce such problems. The development of such an application represents a new solution for merchants and consumers in the pizzeria business in Princesa Isabel and the surrounding region, who seek practicality and convenience when placing orders, providing security and privacy for the parties involved.